THE OPTIMIZATION OF ENZYMATIC SYNTHESIS FOR LAUROYL-N-METHYL GLUCAMIDE SURFACTANTS - Zuhrina Masyithah; Seri Bima Sembiring; Zul Alfian; Tjahjono Herawan (Indonesian Journal of Chemistry, 2011)
The optimization of enzymatic synthesis for lauroyl-N-methyl glucamide surfactants is studied. The fraction of palm kernel oil namely lauric acid (AL) was amidificationed with N-methyl glucamine (MGL) to produce lauroyl-N-methyl glucamide. Study was carried out by using immobilized lipase from Candida antarctica (Novozyme 435®), and tert-amylalcohol as a solvent. Response Surface Methodology (RSM) based on a five level, three variable design was employed, firstly, for studying the interactive effect of various parameters on the reaction, and secondly, for the optimization. The reaction parameters observed were Novozyme concentration, substrate molar ratio, and temperature. Simultaneously increasing Novozyme concentration, substrate molar ratio, and temperature improves the reaction yield and the effect of temperature is noted more significant. The expected optimum condition was at molar ratio MGL:AL 1:1, the Novozyme concentration of 8% and the reaction temperature of 50-55 °C. The reactions at the optimum condition produce the convertion of lauric acid of 64.5% and yield of 96.5%. With the optimization procedure the higher alkyl glucamide yield was achieved.